Linear polarization of a group of symbiotic systems - Brandi, Estela (2000)
We report linear polarization measurements of a set of symbiotic stars, made at several epochs during the period 1994-1998. Evidence of intrinsic polarization is looked for from the wavelength dependence of the polarization degree and position angle in UBVRI bands. The results have also been analysed to search for temporal variability of polarization. Several objects have shown a polarization spectrum different from that produced by interstellar dust grains and/or polarimetric variations on time scales as short as several days or months, indicating the presence of polarization component of circumstellar origin.